Optimizing Perioperative Care for Children and Adolescents with Challenging Behaviors. Issue 3 (May 2015) - Balakas, Karen; Gallaher, Carol S.; Tilley, Carra
<x xml:space="preserve">Abstract</x> Abstract Pediatric perioperative nurses care for a wide variety of children and adolescents, some of whom have special developmental or behavioral needs. Providing care for this vulnerable population can be challenging because they may not express their level of pain or anxiety through behaviors commonly observed in typically developing children. This quality improvement project was conducted to enhance perioperative care delivered to children with challenging behaviors and to their families. A screening tool to individualize the plan of care was developed to identify specific behaviors, triggers, and communication patterns of these children prior to hospitalization. Interventions were identified to address these behaviors that could be used by nurses, child life specialists, and occupational therapists. Partnering with parents and other members of the interprofessional healthcare team has resulted in best practice care planning for these children, ensuring a much more successful perioperative experience for patients and families. Findings from parent surveys demonstrate that by using the tool, nurses and other team members are able to minimize stressors and implement interventions specific to the child. As a result, the adaptive care planning tool has expanded beyond the perioperative area and is now being used by direct care nurses, support staff, nurse practitioners, and physicians across the organization.